2011
DOI: 10.1590/s0100-204x2011001200012
|View full text |Cite
|
Sign up to set email alerts
|

Microbial communities in Cerrado soils under native vegetation subjected to prescribed fire and under pasture

Abstract: The objective of this work was to evaluate the effects of fire regimes and vegetation cover on the structure and dynamics of soil microbial communities, through phospholipid fatty acid (PLFA) analysis. Comparisons were made between native areas with different woody covers ("cerrado stricto sensu" and "campo sujo"), under different fire regimes, and a 20-year-old active palisadegrass pasture in the Central Plateau of Brazil. Microbial biomass was higher in the native plots than in the pasture, and the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 25 publications
2
18
1
1
Order By: Relevance
“…The beginning of the wet season is associated with an increase in microbial biomass (Nardoto and Bustamante 2003;da Silva 2004), microbial activity, organic carbon, and nitrification (da Silva 2004). These changes in soil water content appear to mask the effects of other factors, such as fire, on microbial communities (da Silva 2004;Viana et al 2011). In a study investigating the effects of the first rain events on dry Cerrado soil, denaturing gradient gel electrophoresis (DGGE) analysis and measurement of CO 2 and NO fluxes revealed that the bacterial community structure responds rapidly after artificial water addition (Pinto et al 2006).…”
Section: Soil Bacterial Communities: Effects Of Vegetation Types Andmentioning
confidence: 99%
See 4 more Smart Citations
“…The beginning of the wet season is associated with an increase in microbial biomass (Nardoto and Bustamante 2003;da Silva 2004), microbial activity, organic carbon, and nitrification (da Silva 2004). These changes in soil water content appear to mask the effects of other factors, such as fire, on microbial communities (da Silva 2004;Viana et al 2011). In a study investigating the effects of the first rain events on dry Cerrado soil, denaturing gradient gel electrophoresis (DGGE) analysis and measurement of CO 2 and NO fluxes revealed that the bacterial community structure responds rapidly after artificial water addition (Pinto et al 2006).…”
Section: Soil Bacterial Communities: Effects Of Vegetation Types Andmentioning
confidence: 99%
“…This soil temperature is not lethal to microorganisms (Wells et al 1979); however, long-term effects of fire can include changes in vegetation cover and altered soil characteristics such as pH and nutrient availability. da Silva (2004) and Viana et al (2011) evaluated the effects of prescribed burning on soil microbial communities in two vegetation types of native Cerrado (woodland cerrado and shrubland). Although fire influenced soil moisture and pH, no significant differences were observed between microbial communities in the burned and unburned areas of either vegetation type.…”
Section: Soil Bacterial Communities: Effects Of Vegetation Types Andmentioning
confidence: 99%
See 3 more Smart Citations